2008
DOI: 10.1177/0165025407087210
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parental bonding, fear of failure and stress during class presentations

Abstract: The purpose of the present studies was to test the hypothesis that students' perceptions of parental bonding may be predictive of how individuals approach achievement situations. It was hypothesized that reports of parental overprotection would be predictive of elevated fears and subsequent stress and low achievement compared to perceived parental care. No hypotheses were specified regarding the gender of the parent. In Study 1 participants were 230 elementary school students who were assessed on motivation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 82 publications
2
25
0
8
Order By: Relevance
“…Individuals using a four-point response scale (0 = very unlike, 3 = very like) are asked about their memories concerning the treatment received from their parents up to the age of 16. PBI has been adapted in the Greek language by Sideridis and Kafetsios [27] and has shown acceptable psychometric properties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals using a four-point response scale (0 = very unlike, 3 = very like) are asked about their memories concerning the treatment received from their parents up to the age of 16. PBI has been adapted in the Greek language by Sideridis and Kafetsios [27] and has shown acceptable psychometric properties.…”
Section: Methodsmentioning
confidence: 99%
“…However, no analysis was conducted on issues related to the suitability of the measure for this specific age population. Similarly, Sideridis and Kafetsios [27] have used an adapted version of the PBI with 5th and 6th graders and found moderate to high reliabilities for Overprotection (0.65) and Caring (0.79) sub-scales, and significant associations with measures of fear of failure, anxiety and depression. However, the suitability of the adapted instrument for the specific age population was not tested further.…”
Section: Introductionmentioning
confidence: 93%
“…These authors suggest that typical stressors in school settings are aggressions, social evaluation and school failure. School anxiety can generate poorer learning results (Chapell & Overton, 1998), poorer performance in evaluative situations (Sideridis & Kafetsios, 2008) and grade retention (King, Ollendick, & Prins, 2000). School anxiety is also associated with psychosomatic symptoms, affecting students' wellbeing and health (King et al, 2000;Von Gontard, Moritz, Thome-Granz, & Equit, 2015).…”
Section: Parenting Style and School Anxietymentioning
confidence: 99%
“…Powers and Wagner (1984) found that internal, ego-related attributions, such as effort and ability, were significantly positively correlated with achievement motivation (r = .31, p < .001), whereas external, causal attributions, such as context and luck, were not. Sideridis and Kafetsios (2008) found that perceptions of parental care, specifically care from mother and care from father, correlated negatively with fear of devaluing self (r = -.30, p < .01; r = -.35, p < .01), fear of uncertain future (r = -.18, p < .01; r = -.23, p < .01) and fear of others losing interest (r = -.28, p < .01; r = -.27, p < .01). A cluster analysis by Paulson, Marchant and Rothlisberg (1998) revealed that students who reported a positive view of parental involvement, such as perceived authoritative parenting, also reported the highest feelings of academic competence and school achievement.…”
mentioning
confidence: 99%
“…Spera (2006) focused on scholastic outcomes rather than the achievement motivation that could lead to these. Sideridis and Kafetsios (2008) hypothesized that fear of failure would mediate the relationship between parental attachment and stress. Paulson, et al (1998) looked at perceptions of academic performance rather than achievement motivation.…”
mentioning
confidence: 99%